Study of the Properties of Foaming Agents Ufapore gp xp 75%, Omax ks100 and Frem Foam for Foam Concrete - Nemat , Muhammadiev; Urinbek , Turgunbaev; Valijon, Bekkulov (Academia Open, 2025)
The article examines the main properties of foaming agents UFAPORE GP XP 75%, OMAX KS100 and FREM FOAM such as - high expansion and durability, sufficient foam durability in solution, durability of the mixture over time. The results of the analysis of the stability, expansion rate and mechanical strength of the foam made it possible to determine the optimal concentrations of the FREM FOAM foaming agent, at which the foam demonstrates the best technological characteristics. To assess the effect of binders and fillers on the foam volume, the foam utilization factor (FUF) was calculated, which is the ratio of the volume of the foam-cement mixture to the initial volume of foam. It is believed that high-quality foam should have a FUF in the range of 0.8–0.85. Initial experiments showed that at surfactant concentrations of up to 0.5%, the foam mass is insufficient to obtain foam-cement masses with constant properties. At the same time, at concentrations over 2.5%, there is excessive consumption of foaming agent, which leads to a violation of the homogeneity of the foam structure. As a result, the optimal range of foaming agent concentrations from 0.5 to 2.5% was selected. Highlights: Examines properties of foaming agents: expansion, durability, and stability. Determines optimal FREM FOAM concentrations for best foam characteristics. Identifies optimal foam utilization factor range (0.8–0.85) for quality foam. Keywords - foaming agent, non-autoclave, foam, porous , foam mass , foaming agent multiplicity.